Beamforming of antenna systems of mimo technology of lte network - Хлапонін, Юрій Іванович (Eastern-European Journal of Enterprise Technologies, 2015)
An analysis of introducing the fourth-generation (4G) cellular networks, the best of which, according to the International Telecommunications Union, are LTE-Advanced1 (based on cellular LTE (Long Term Evolution) standard) and WirelessMAN-Advanced2 (based on WiMAX 802.16m) technologies, is presented in the paper. A further increase in throughput and service quality in LTE networks is associated with MIMO. Abbreviation MIMO means "multiple input, multiple output". The aim of the research was to develop a method for increasing the throughput in the MIMO system of the LTE network by beamforming with physical separation of antenna elements. The beamforming method for increasing the throughput in the MIMO system of the LTE network was proposed. A block diagram of beamforming of the multi-user system was presented. To compare throughput, simulation with without beamforming for two types of flow transfer modulation using the Matlab program was conducted. The scientific basis of increasing the throughput in the MIMO system of the LTE network, developed in the paper may be taken into account when designing modern data transmission systems based on intelligent technologies.